PATHOGENETIC ASPECTS OF OVARIAN POLYCYSTOSIS SYNDROME IN PATIENTS WITH METABOLIC DISORDERS - Urunova Farangiz; Abdullaeva Raykhon; Rasulova Mokhinur; Negmatova G. Sh. (Web of Journals Publishing, 2025)
Polycystic ovary syndrome (PCOS) is a common hormonal disorder that occurs most often in women of reproductive age. The main signs of ovarian polycystic disease include menstrual cycle disorders, irregular ovulation, high levels of androgen hormones in the blood, and a specific polycystic structure of the ovaries according to ultrasound results [1,6].
Keywords: Polycystic ovary, metabolic disorders, pathogenesis, diagnosis, follicles, obesity.